Mixed Convection Flow from Vertical Plate Embedded in Non-Newtonian Fluid Saturated Non- Darcy Porous Medium with Thermal Dispersion-Radiation and Melting Effects - b.d.c.n. prasad; K. Hemalatha; J. Siva Ram Prasad (Journal of Applied Fluid Mechanics, 2014)
We analyzed in this paper the problem of mixed convection along a vertical plate in a non-Newtonian fluid saturated non-Darcy porous medium in the presence of melting and thermal dispersion-radiation effects for aiding and opposing external flows. Similarity solution for the governing equations is obtained for the flow equations in steady state. The equations are numerically solved by using Runge-Kutta fourth order method coupled with shouting technique. The effects of melting, thermal dispersion, radiation, temperature ratio, inertia and mixed convection on velocity distribution and temperature are examined for aiding and opposing external flows.